CORRELATION BETWEEN THE KNOWLEDGE OF ECOSYSTEM AND ENVIRONMENTAL ETHICS WITH STUDENTS PARTICIPATION IN ENVIRONMENTAL HYGIENE IN JAMBI CITY, INDONESIA - Esty Komariah; Yossa Istiadi; Eka Suhardi (Journal of Science Innovare, 2022)
The objectives of the research is to find the correlation between the knowledge of ecosystem  and environmental ethics with students participation in environmental hygiene.  The research was conducted at the Junior High School in District Telanaipura, Jambi City, with a sample of 107 students were taken by proportional random sampling. The research used survey method and data analysis technique using the correlation and simple linier regression statistic test, the hypothesis test was conducted on a 0.05 and 0.01significance level. The research produced three main conclusion i.e. First, there is a significant positive correlation between the knowledge of the ecosystem (X1) with hygienic behavior (Y)coefficient ry1 = 0.777 and regression equation Ŷ = 28.794 + 0.730 X1. Secondly, there is a significant positive correlation between Environmental Ethics (X2) with hygienic behavior (Y) with ry2 correlation coefficient = 0.790, the regression equation Y = 21.250 + 0.745 X2. Thirdly, there is a significant positive correlation between knowledge about the ecosystem (X1) and Environmental Ethics (X2) together with hygienic behavior (Y) with ry.12 correlation coefficient = 0.790 and the regression equation Y = 19.522 + 0.284 X1 + 0.477 X2. Based on the results of this study concluded that a hygiene life behavior can be improved through knowledge about the ecosystem and environmental ethics